Exploring the Effect of Maternal Physical Activity and Placental Region on Mitochondrial Protein Content and Function in the Placenta - Rankin, Jonathan (Université d'Ottawa / University of Ottawa, 2019)
The placenta is responsible for mediating fetal growth and development, thereby influencing health across the lifespan. Physical activity (PA) confers benefits to mother and baby during pregnancy, but little is known about its impact on the placenta. There were two purposes of this study: i) to determine if maternal PA during pregnancy influences placenta mitochondrial protein content and function, and ii) to determine if there were differences in placenta mitochondrial protein content and function in different regions of the placenta, namely proximal or distal to the centre of the placenta. Healthy women between 12-28 weeks gestation were recruited, and free-living PA was objectively assessed at multiple time points during pregnancy using an accelerometer. Participants were grouped by minutes of moderate-to-vigorous PA (MVPA) per day. Placenta tissue samples were collected from central and distal placental regions immediately post-birth and were used for two separate analyses. Half of the samples were flash frozen in liquid nitrogen and used for western blot analysis of mitochondrial complex I-V proteins. Fresh mitochondria were isolated from the other half of the samples, and high-resolution respirometry was used to measure placental mitochondrial respiration. There were significant positive correlations between maternal PA and mitochondrial protein content in peripheral tissue samples, but protein content was significantly higher in central tissue compared to peripheral tissue samples. In addition, state 3 respiration was higher in central tissue samples of placentas from participants with high MVPA compared to participants with low MVPA. Finally, complex I protein was higher in central tissue samples of placentas from female offspring compared to placentas of male offspring. However, many of these results are underpowered and further study is warranted. This study provides new avenues to explore the relationship between PA and placenta mitochondria in healthy populations.
Keywords: Placenta; Pregnancy; Physical Activity; Mitochondria